Meltdown a global warming journey - Paul, Rose; Renouf, Jonathan; Goodchild, Marc; British Broadcasting Corporation (London BBC Worldwide Limited, 2009)
"This program studies divergent points of view contributing to the global warming debate, untangling a morass of political and scientific concerns and providing a wealth of historical background on the issue"--Container
Originally produced as a BBC documentary in 2006
Keywords: Global warming; Global temperature changes; Greenhouse effect, Atmospheric; Documentary television programs